New Antioxidant Flavonoids from the Aerial Parts of Secamone Afzelii - Abdulmagid Alabdul Magid; Philomène Akoua Yao-Kouassi; Diane Patricia Apie Gossan; Claire Mairot; Laurence Voutquenne-Nazabadioko (Journal of Antioxidant Activity, 2016)
A bioassay-guided fractionation of petroleum ether, EtOAc and n-BuOH soluble parts of the 80% hydromethanol extract was performed to investigate the antioxidant activity of Secamoneafzeliiaerial parts using DPPH free radical scavenging assay. The results revealed that EtOAc and n-BuOH soluble parts have moderate to good DPPH radical scavenging activity (EC50 = 139.3 and 30.5 μg/mL, respectively). Therefore, from the most active fractions of EtOAc and n-BuOH soluble parts were isolated two new flavonoid diglycosides quercetin-3-O-β-d-apiofuranosyl-(1→2)-α-l-rhamnopyranoside and genkwanin-8-C-β-d-apiofuranosyl-(1→2)-β-d-glucopyranoside in addition to nine known compounds (2-10). Their structures were elucidated on the basis of spectroscopic data including 1D- and 2D-NMR and ESI-MS. The ability of the isolated compounds to scavenge the DPPH was evaluated. The new compound 1, quercitrin (3) and rutin (6) have antioxidant potential with EC50 values ranging from 8.4 to 13.6 µg/mL, compared to the standard ascorbic acid (EC50 7.4 µg/mL).
Keywords: Secamoneafzelii